Letter to Rosa Hill from William Strickland, January 21, 1916 - Strickland, William (Valdosta State University Archives and Special Collections, 1916)
Letter to Rosa Hill from William Strickland, January 21, 1916. To: Hill, Rosa From: Strickland, William Description: letter celebrating the first anniversary of their marriage.
1 Electronic record(s) and derivatives. `hudson_letter_040.pdf` 2 pages. 1441797 bytes.
Keywords: Letters